Public Compliance with Face Mask Use in Honolulu and Regional Variation - Tamamoto, Kasey A; Rousslang, Nikki D; Ahn, Hyeong Jun; Better, Heidi E; Hong, Robert A (Hawai'i journal of health & social welfare, 2020)
Infections with the SARS-CoV-2 virus are increasing in Hawai'i at alarming rates. In the absence of a SARS-CoV-2 virus vaccine, the options for control include social distancing, improved hygiene, and face mask use. There is evidence that mask use may decrease the rates of viral transmission. The rate of effective face mask use has not yet been established in Hawai'i. The authors performed an observational study at 2 locations in Honolulu and evaluated outdoor face mask use compliance in 200 people. Simultaneous observations were performed in a downtown Honolulu business area and in Waikiki, an area focusing on tourism. Overall, 77% of all subjects used face masks in an appropriate fashion, covering their nose and mouth, while 23% were either incorrectly masked or not masked. The rate of compliance with correct public mask use in downtown Honolulu (88%) was significantly higher than in Waikiki (66%) (P=.0003, Odds Ratio [95% Confidence Interval]=3.78 [1.82, 7.85]) These findings suggest that there are opportunities for improvement in rates of public face mask use and a potential decrease in the spread of COVID-19 in our population. Four proposed actions are suggested, including a reassessment of the face mask exemption requirements, enhanced mask compliance education, non-threatening communication for non-compliance, and centralization of information of the public compliance with face mask use.